Macrobrachium Spence Bate, 1868 (Decapoda: Palaemonidae): New records, range extension and geographic distribution in the Northeastern Caatinga & Coastal Drainages, and São Francisco hydrographic ecoregions, Northeast of Brazil - Moraes, Alex Barbosa De; Moraes, Daniele Cosme Soares De; Alencar, Carlos Eduardo Rocha Duarte; Pinheiro, Allysson Pontes; Lima, Sergio Maia Queiroz; Freire, Fúlvio Aurélio De Morais (Zootaxa, 2021)
This study constitutes the most comprehensive effort ever done to assess the faunal diversity of the Macrobrachium genus within two ecoregions that encompass part of the northeastern Brazil: the Northeastern Caatinga & Coastal Drainages, and the São Francisco (Lower-middle and Lower portions). Through sampling in several of their hydrographic basins, bibliographic research, and consulting scientific collections, our results reveal the occurrence of five species along these ecoregions: Macrobrachium acanthurus, M. amazonicum, M. carcinus, M. jelskii and M. olfersii. We also provide the first record of these species for several river basins in both ecoregions. Additionally, we confirm the occurrence of M. carcinus from Rio Grande do Norte State and provide updated distribution maps for each species in the studied area. This carcinofauna survey may form the basis for future evaluations of eventual anthropic impacts on biological diversity resulting from projects being implemented in these regions, which involve the São Francisco interbasin water transfer.